2021
DOI: 10.1177/1098612x211044412
|View full text |Cite
|
Sign up to set email alerts
|

Technology-enhanced weight-loss program in multiple-cat households: a randomized controlled trial

Abstract: Objectives The objectives of this study were to determine whether a technology-enhanced weight-loss program, using a home pet health technology ecosystem, is an effective tool in feline weight-loss management in multiple-cat households and to evaluate its impact on cat behavior. Methods The study was a prospective parallel unmasked block-randomized controlled trial comparing two weight loss intervention groups: (1) traditional group with dietary restriction alone (n = 9); (2) technology group that used dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge, few studies have shown improvement in perceived QoL in cats after a WLP; [12][13][14] nonetheless, one study 14 compared perceived QoL with BCS and %WL/ week, and did not find a statistical correlation with the cats' QoL. Additionally, there are no published data assessing the difficulties encountered by owners during WLP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, few studies have shown improvement in perceived QoL in cats after a WLP; [12][13][14] nonetheless, one study 14 compared perceived QoL with BCS and %WL/ week, and did not find a statistical correlation with the cats' QoL. Additionally, there are no published data assessing the difficulties encountered by owners during WLP.…”
Section: Discussionmentioning
confidence: 96%
“…35 Giving treats is common in feeding regimens, 36,37 and positively affects the owner's psychological health; 38 however, it can increase EI and is a risk factor for obesity. 15,39,40 No treats were included in the present study; however, anecdotal data suggest a possibility of treat feeding <10% EI 14,41,42 without causing nutritional imbalances. 41 To overcome this difficulty,…”
Section: Difficultiesmentioning
confidence: 99%
“…"The study was a prospective parallel unmasked blockrandomized controlled trial comparing two weight loss intervention groups: (1) traditional group with dietary restriction alone (n = 9); (2) technology group that used dietary restriction, digital scales, smart feeders, activity monitors and pet treat cameras (n = 6)." (33) "A randomized crossover study was performed. Dogs received either sildenafil (1 mg/kg, PO, q 12 h) or a placebo for 14 days, followed by a 7-day washout period, then the opposite treatment for 14 days."…”
Section: Methods Trial Designmentioning
confidence: 99%
“…For cats in multiple-pet households, microchip feeders as well as separating pets at mealtimes can reduce competition for food and overconsumption. 96 98 A recent consensus statement recommends feeding cats multiple small meals per day to mitigate behavioral concerns and potentially improve welfare; 97 however, once-a-day feeding may be beneficial in promoting satiety and fatty acid oxidation in cats compared with multiple feedings. 29 To date, there is a dearth of data investigating the long-term physiological effects of feeding frequency in cats and its role in obesity prevention.…”
Section: Obesity Prevention Strategies For Kittensmentioning
confidence: 99%